1993
DOI: 10.1038/361650a0
|View full text |Cite|
|
Sign up to set email alerts
|

Use of evolutionary limitations of HIV-1 multidrug resistance to optimize therapy

Abstract: Wild-type reverse transcriptase has evolved for the survival of human immunodeficiency virus type 1 (HIV-1) by natural selection. In contrast, therapy relying on inhibitors of reverse transcriptase by nucleosides like zidovudine (AZT) or dideoxyinosine (ddI), and by non-nucleosides like pyridinones or nevirapine, may exert different selection pressures on this enzyme. Therefore the acquisition of resistance to reverse transcriptase inhibitors by selection of mutations in the pol gene may require compromises in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(45 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…This, of course, will reduce the time period over which therapy can be administered. New research suggests that combination drug treatments is preferable since there is a reduced chance of the virus mutating simultaneously to strains resistant to all of the drugs present in the 'cocktail' [6,27]. We are presently exploring these phenomena through a revised model.…”
Section: Discussionmentioning
confidence: 99%
“…This, of course, will reduce the time period over which therapy can be administered. New research suggests that combination drug treatments is preferable since there is a reduced chance of the virus mutating simultaneously to strains resistant to all of the drugs present in the 'cocktail' [6,27]. We are presently exploring these phenomena through a revised model.…”
Section: Discussionmentioning
confidence: 99%
“…How can we reconcile the above observations with those of Chow et al (1993a)? One possibility was that the replication-defective triple mutant reported was nonviable for reasons other than the presence of the four resistance mutations.…”
Section: Convergent Therapy or Multi-drug Resistance?mentioning
confidence: 98%
“…However, Chow et al (1993a) reported that mutant virus containing substitutions conferring resistance to AZT (T215Y, K219Q) and ddI (L74V) became non-viable when an NNRTI resistance mutation (K103N) was added. This prompted speculation that so-called convergent combination therapy would not result in simultaneous resistance to AZT, ddI and an NNRTI such as nevirapine.…”
Section: Convergent Therapy or Multi-drug Resistance?mentioning
confidence: 99%
“…Some groups have proposed that convergent combination therapy may be the most appropriate for the treatment of HIV infections, by virtue of the fact that multiple mutations in the same viral gene should cause the total compromise of an essential viral enzyme function. Theoretically this should prevent the development of multi-drug resistance (Chow et al, 1993). It appears, however, that multi-drug-resistant variants can still be selected during such combination therapy (Emini et al, 1993;Larder et al, 1993).…”
Section: Discussionmentioning
confidence: 99%